Islamic Bank Financing and Its Effects on Economic Growth: A Cross Province Analysis - Muhammad Anif Afandi; Muhammad Amin (Signifikan: Jurnal Ilmu Ekonomi, 2019)
Islamic banking industry shows a reasonably good development, one of which is marked by an increase in service coverage in almost all provinces in Indonesia. However, the question is how far Islamic banking capable of contributing to the improvement of Indonesia's economic growth? The purpose of this research is to examine the role of Islamic banking in promoting inclusive economic growth with a sample of 33 provinces in Indonesia. The method used in this research is panel data regression using the fixed effects model. The results show that Islamic bank financing does not have an impact on Indonesia's economic growth. In other words, the results of the research provide information that the existence of Islamic banking in Indonesia has not yet give a significant impact on the welfare of Indonesian society